Leakage Management Influence on Water Age of Water Distribution Networks - Orazio Giustolisi; Francesco G. Ciliberti; Luigi Berardi; Daniele Biagio Laucelli (Water Resources Research, 2023)
Abstract Leakage management of Water Distribution Networks (WDNs) is a relevant technical task worldwide. Background leakages along mains and connections to properties in aged infrastructures represent a significant portion of the WDN water outflow, sometimes exceeding customer demands. Pressure control and District Metering Areas (DMAs) design are two classic activities aimed at leakage management. The former reduces the background leakages, and thus the velocities in pipes, especially those along main paths for water transport across the WDN. The latter involves closed valves confining each DMA, which change network connectivity reducing redundancy and eventually pressure, that is, background leakages. Hence, both activities reduce water velocity in pipes because of leakage reduction (i.e., the overall WDN inflow), while DMAs could increase it in some pipes. Therefore, leakage management activities might affect the water age in WDNs, as a general water quality indicator, depending on the initial level of leakages, the WDN connectivity and topology, and the attained reduction. This work studies the effect of leakage management on water age for two real WDNs, which are characterized by different initial levels of leakages and expected reduction, after planning pressure control and DMAs. The advanced hydraulic modeling, employing pressure‐driven leakage modeling at pipe level, is integrated with water age analysis, allowing unlimited number of parcels. The sensitivity of water age to the maximum number of parcels in the model is studied to identify the trade‐off between accuracy and computational runtime. The variation of mean daily water age due to change of demand pattern is analyzed considering a 4‐week operative cycle.